A Qualitative Study of Eating Behaviour among On-Campus Students at a Malaysian Public University - Mat Issa, Zuraini; Nizamuddin, Mohammad Nazrin; Abd Nasir, Ammar Daniel; Farapti, Farapti (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study explores factors influencing the eating habits of on-campus university students. A qualitative research design using semi-structured interviews was involving eight students residing in on-campus accommodation. Thematic analysis followed Braun and Clarke’s reflexive model and identified four main themes, namely limited food variety, convenience, health-consciousness and financial constraints. Meanwhile, food presentation was identified as a sub-theme of the limited food variety theme. Students reported limited food variety due to minimal dining options, leading to repetitive diets and dissatisfaction. Convenience was a key factor, with students choosing foods that were affordable and readily available. Some made health-conscious decisions to reduce unhealthy food intake but simultaneously increased consumption of protein-rich foods like red meat and full-fat dairy—potentially leading to high saturated fat and calorie intake. Financial constraints also played a role, with students often selecting inexpensive, less nutritious options. Hence, food presentation emerged as an important sub-theme and influence, with students showing a preference for colourful and visually appealing meals, regardless of nutritional quality. The findings highlight the need for universities to enhance food variety, accessibility, and affordability. Institutions could collaborate with food vendors to provide rotating menus and coordinate with zakat centres to support students financially through subsidised meals. Food and nutrition education should also be implemented to help students make informed dietary choices. Future research should include a more diverse student population to build a broader understanding of these issues.